SIFAT PAPAN PARTIKEL DAUR ULANG RENDAH EMISI FORMALDEHIDA - Adi Santoso; Gustan Pari (Jurnal Penelitian Hasil Hutan, 2015)
Formaldehyde emission and physical-mechanical properties of particleboard bonded with urea formaldehyde (UF) could have negative effects on human health, specially when used in a room with limited ventilation. To reduce formaldehyde emission, an adsorbent can be added into adhesive mixture. This report describes the effect of imposing active charcoal into urea formaldehyde adhesive in terms of formaldehyde emission, physical-mechanical changes and economic aspect of the recycled particleboard. Results showed that the addition of active charcoal in particleboard production significantly changed the product properties. The charcoal addition as much as 3% to the UF adhesive could reduce formaldehyde emission and improve physical-mechanical properties of particleboard, and meet the Indonesian and Japanese Standards. The addition of active charcoal into particleboard is financially feasible.